Optimization on extraction technology of bacteriostatic extract from Indocalamus leaves and its bacteriostatic test - LIU Li-ping; XU Peng; LEI Xiao-hong; WANG Ning; YANG Bing (Shipin yu jixie, 2022)
Objective: To study and optimize the extraction technology of bacteriostatic extract from Indocalamus leaves. Methods: The extracts were drawn from Indocalamus leaves by ultrasound-assisted, refluxing and immersing method with extraction solvents: water, ethyl acetate, pH 4 of hydrochloric acid solution, pH 4 of acetic acid solution, pH 10 of ammonia solution and different volume ratio ethyl alcohol. The tests were carried out to analyze the antimicrobial effects with indicator bacteria Bacillus subtilis, Pseudomonas aeruginosa, Shigella Dysenteriae and Salmonella typhi and the total bacteriostatic circle was as inspection indicator, to find out the best extraction solvent and the best extraction method. Using water as extraction solvent, ultrasonic extraction method as method, an orthogonal test L9（33） was carried out by adjusting three impact factors. The impact factors were liquid-solid ratio, sonication period and sonication frequency. The orthogonal test found the optimal extraction process parameters and obtained the best extract. At the same time, the antimicrobial effect of the extract obtained under the optimized conditions was investigated according to the standard series of reference substances. Results: The results showed that water was the best solvent, and ultrasound-assisted method was the best method. The best extraction process parameters were as follows: the ratio of liquid to solid was 16∶1 （mL/g）, ultrasonic frequency was 4 times, ultrasonic period was 55 minutes. The inhibitory effect of the best extract on Bacillus Subtilis and Salmonella Typhi was equivalent to the effect of 0.01 and 0.03 mg/mL gentamicin, respectively. The bacteriostatic effects on Pseudomonas Aeruginosa and Shigella Dysenteriae were greater than that of 0.05 mg/mL gentamicin. Conclusion: The water ultrasonic method is an effective method for extracting antibacterial substances from Indocalamus leaves, and the inhibitive effect of the extract on Bacillus Subtilis, Pseudomonas Aeruginosa, Shigella Dysenteriae and Salmonella Typhi is remarkable.